Emotional Intelligence, Self-Efficacy and Empathy as Predictors of Overall Self-Esteem in Nursing by Years of Experience - Pérez-Fuentes, María del Carmen; Molero Jurado, María del Mar; del Pino, Rosa María; Gázquez Linares, José Jesús (Frontiers in Psychology, 2019)
Empirical research on self-esteem has a special interest in nursing professionals, because they work in a challenging environment that requires, in order to continue working during their working age, a strong physical, social and emotional involvement. The objective was to determine the explanatory value of individual variables such as Self-efficacy, Empathy and Emotional Intelligence on Self-esteem in a sample of nursing professionals, to identify which variables have the most explanatory value for overall self-esteem with years of experience. The study sample consisted of a total of 1601 Spanish nurses aged 22 to 60, with a mean age of 31.19 (SD=6.59) years. The emotional intelligence factors in all cases were observed to have positive correlations with overall self-esteem. Mood was still the predictor with the most explanatory weight in all the groups. General Self-Efficacy disappeared in the model of professionals with the most experience. Organizations and management nursing should implement intervention programs that promote wellbeing and satisfaction in workers during their working age. It would be of interest to train nursing professionals in such necessary competences as Empathy, Emotional Intelligence and Self-Efficacy.